Highly Enhanced Visible‐light Photocatalytic Activity via a Novel Surface Structure of CeO2/g−C3N4 toward Removal of 2, 4‐dichlorophenol and Cr(VI). Issue 8 (19th February 2021) - Guo, Lei; Yang, Jingxia; Zhang, Huiqing; Wang, Runkai; Xu, Jingli; Wang, Jinjie
Abstract: Photocatalysis is an efficient and eco‐friendly method of solving the environmental problems, but the low charge separation efficiency of photocatalysts limits their application. Herein, we report the fabrication of CeO2 /g−C3 N4 composites via an in‐situ growth of CeO2 on the dispersed g−C3 N4 sheets (CN−OH) in an strong KOH condition, and the resultant CeO2 /CN−OH composites set up a new interface structure, which demonstrate a dramatically boosted the photocatalytic activity compared with CeO2 /g−C3 N4 composites by conventional two‐step combination method. The decomposition efficiency of CeO2 /CN−OH for 2, 4‐dichlorophenol (2, 4‐DCP) degradation comes up to 6 times of bare CeO2 or g−C3 N4 . Compared to conventional CeO2 /g−C3 N4, the CeO2 /CN−OH showed 65.9 % and 23.2 % improvement for 2, 4‐DCP and Cr(VI) removal, respectively. The significantly enhanced photodegradation ascribe to the alkaline modified CN−OH and the fabrication of CeO2 /CN−OH n–n type heterojunction, both can improve the charge separation efficiency and increase the reaction active sites. Furthermore, the probable pathway and concreted photocatalytic mechanism for 2, 4‐DCP degradation are proposed based on the detected intermediate products. Abstract : The rule of seven : The brilliant photocatalytic performance of CN−OH/CeO2 −NP is due to the synergistic improvement of surface structure. The heptazine ring of g−C3 N4 can establish a consummate complexing with K ion. Moreover, unsaturated‐coordination O between CN−OH/CeO2 −NP composite can establish a firmly interfacial interaction with g−C3 N4 nanosheets by p–π bond. Furthermore, the hydroxyl groups on the surface of ceria can form hydrogen bond with the NOH/NHx group of g−C3 N4 nanosheets.